Giant Basal Cell Carcinomas Arising on the Bilateral Forearms of a Patient: A Case Report and Review of Nonsurgical Treatment Options - Sarah Shangraw; Rivka C. Stone; Jeong Hee Cho-Vega; Robert S. Kirsner (Karger Publishers, 2016)
Giant basal cell carcinomas (GBCCs) are large basal cell carcinomas (BCCs; <5 cm) with a greater propensity to invade and metastasize than standard BCCs. The presence of 2 GBCCs in a single individual is rare. We present the case of a 71-year-old Caucasian male with bilateral GBCCs on the dorsal forearms, measuring 130 cm2 and 24 cm2, respectively, that developed over a 21-year period. Over this period, the patient treated the tumors with herbal remedies. Histologic evaluation showed a conventional nodular BCC for both tumors. Computed tomography and magnetic resonance imaging revealed a T4N0M0 stage for the larger lesion. Surgical excision and grafting and reconstruction were offered, but he declined. This case highlights a shared belief in holistic treatments and rejection of Western medical interventions that are common among many patients with GBCC. Studies reporting nonsurgical treatments for GBCCs, including radiotherapy, vismodegib, topical imiquimod, and acitretin are reviewed.